Analysis Factor Associated Tuberculin Test in Children Contact Tuberculosis History - Tika Triharinni; Muhammad Atoillah Isvandiari (Universitas Airlangga, 2014)
ABSTRACT Tuberculosis in children can not be separated from the history of contact with smear-positive tuberculosis patients as a source of infection. The aims of this study was to identify and analyze the risks tuberculin test results among children who had contact with patients with smear-positive tuberculosis in health center Bangil and health center Raci Pasuruan. The design of this study was cross sectional using systematik random sampling technique. Sample were drown from children with history of contacts with smear positive tuberculosis patients during 2012. This studies was from January until Juni 2013. The independent variables included age, sex, BCG immunization status, nutritional status, the average duration of exposure per day and residential density, the dependent variable was the tuberculin test results. It was found that from the study the results that a positive tuberculin test result was 28.57%. There was a significant relationship between age, nutritional status, the average duration of exposure per day, residential density of the tuberculin test, and there was no significant relationship between sex and status of BCG immunization results and tuberculin test results. Male and a dense residential density increases the risk of a positive tuberculin test results. While a good nutritional status is a protective factor for tuberculin test result positive. Keywords: tuberculin test, children, history of contacts of smear positive